Discovering the Legacy of Mandailing Ulama: Education, Intellectuals, and Politics in North Sumatra in the Early 20th Century - Ja'far Ja'far; Mhd. Syahnan; Asrul Asrul; Zaini Dahlan; Sakti Ritonga (Universitas Islam Negeri Mataram, 2022)
This study examines the role of Mandailing ulama in education, intellectuals, and politics in the early 20th century. Ulama plays a critical role in safeguarding the morality of Muslim society (umma). Drawing upon the historical approach, it employed Kuntowijoyo model of writing history stages and Anthony Giddens' structuration theory to analyze the problems that this study intends to answer. This study argues that the social structure surrounding the Mandailing ulama enabled them to address religious and other sociocultural issues. This study also unveiled that the Mandaling ulama in the early 20th century mobilized the organizations, such as Al Washliyah (1930), Al-Ittihadiyah (1935), and Nahdlatul Ulama (1918) to promote the education of the indigenous people, fortify the Sunni school of thought from the heretical and influence of Dutch colonial government. It was manifested by supporting only two Islamic political parties: the Masjumi Party and the Nahdlatul Ulama Party. This suggests that Ulama were not only religious scholars who acquired knowledge of Islamic norms and disseminated them through religious and educational institutions, such as madrasa and pesantren, but also active agents in socio-political transformation within the Muslim community.